Influence of precipitates on basal dislocation slip and twinning in AZ91 micro-pillars. Issue 23 (1st December 2020) - Si, S.; Wu, J.; Jones, I. P.; Chiu, Y. L.
ABSTRACT: Micro-pillars of solution-treated and aged AZ91 magnesium alloy (Mg-9Al-0.7Zn-0.2Mn) have been used to study the influence of precipitates on plastic deformation mechanisms. The micro-pillars were compressed along [ 55 10 ¯ 9 ] and [ 01 1 ¯ 0 ] directions in order to activate basal slip and 01 1 ¯ 2 twinning, respectively. The critical resolved shear stresses were determined. Precipitates had limited strengthening effect on basal slip, but increased significantly the stress required for twin growth. The precipitates are engulfed by the tension twins during deformation. The back stress generated due to the presence of the precipitates is expected to provide a considerable contribution to strengthening which slows the twin growth. A high density of stacking faults was observed in the aged specimen, particularly in between the precipitates, which may hinder dislocation glide upon further deformation.